Temporal analysis of the relationship between leptospirosis, rainfall levels and seasonality, Santa Catarina, Brazil, 2005-2015 - Ghizzo Filho, João; Nazário, Nazaré Otília; Freitas, Paulo Fontoura; Pinto, Gustavo de Araújo; Schlindwein, Aline Daiane (Revista do Instituto de Medicina Tropical de São Paulo, 2018)
The objective of the study is to analyze the temporal trend of leptospirosis incidence, according to rainfall levels in Santa Catarina, according to seasonality, from 2005 to 2015. This is an ecological study of time series, with date of leptospirosis, rainfall levels and population. The incidence rates of leptospirosis, relative excess of incidence, Pearson’s correlation coefficient (r) and an angular coefficient (β) were analyzed from the linear regression adjustment, with a 5% significance level. Distribution of leptospirosis cases, rainfall levels and cases reason/rainfall levels, stratified by month of occurrence were presented. There were 5,274 cases of leptospirosis, with the monthly average being 439 cases, ranging from 211 in September to 770 in January. The mean rate of leptospirosis was 7.03 per 100,000 habitants. The average rainfall level was 158.68 mm, with the lowest levels occurring in August, average of 124.9 mm, and the highest in January average of 213.20 mm. The positive correlation between leptospirosis rates and rainfall levels, during the period from January to December (r = 0.68, p = 0.023), indicates a positive temporal association between the amount of rainfall and the cases of the disease. The disease occurred all year round and presented a distinct seasonality from October to March.